2014
DOI: 10.1136/bcr-2013-202220
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spectral domain optical coherence tomography in chronic exposure to welding arc

Abstract: SUMMARYThree-dimensional spectral domain optical coherence tomography was performed in a 26-year-old man with chronic exposure to welding arc. Advanced macular visualisation provided significant findings of inner segment-ellipsoid zone disruption with the presence of cystoid changes and hyper-reflective material in the area of disruption. The external limiting membrane was intact in both the eyes. C-scan retinal pigment epithelium fit map of the left eye revealed a well-delineated defect whereas the right eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…However, hyper-reflectivity in the external limiting membrane became apparent on OCT in their patients after 1 month 6. Other studies reported the OCT findings of chronic welding arc maculopathy as interruption in the IS/OS layer and the inner portion of the RPE 3 11 12. Saxena et al reported hyper-reflective material deposit in the disrupted region which may have resulted from reduced phagocytosis of RPE and increased accumulation of the cone OS 12.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, hyper-reflectivity in the external limiting membrane became apparent on OCT in their patients after 1 month 6. Other studies reported the OCT findings of chronic welding arc maculopathy as interruption in the IS/OS layer and the inner portion of the RPE 3 11 12. Saxena et al reported hyper-reflective material deposit in the disrupted region which may have resulted from reduced phagocytosis of RPE and increased accumulation of the cone OS 12.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies reported the OCT findings of chronic welding arc maculopathy as interruption in the IS/OS layer and the inner portion of the RPE 3 11 12. Saxena et al reported hyper-reflective material deposit in the disrupted region which may have resulted from reduced phagocytosis of RPE and increased accumulation of the cone OS 12. Although the prognosis of welding-induced photic retinal injury is usually good, permanent complications are sometimes reported,9 and this difference in sequelae may reflect the severity of exposure and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Welding arcs can cause phototoxic macular injuries largely indistinguishable from solar retinopathy, as shown in Fig. 8a [136,[210][211][212][213]. Retinal temperature increases are typically too low for photocoagulation [6,133], but thermal damage may be involved in severe injuries [214,215].…”
Section: Welder's and Flash Maculopathymentioning
confidence: 99%